Efficacy and safety of G-CSF, low-dose cytarabine and aclarubicin in combination with l-asparaginase, prednisone in the treatment of refractory or relapsed acute lymphoblastic leukemia. (November 2017) - Zhou, Keshu; Song, Yongping; Zhang, Yanli; Wei, Xudong; Fu, Yuewen; Yu, Fengkuan; Zhou, Hu; Liu, Xinjian; Zhou, Jian; Fang, Baijun
Highlights: The overall response rate and complete remission rate were 86.1% and 63.9% respectively. The median overall survival from CAGLP treatment was 16 months. A subset of patients underwent stem cell transplant achieved longer overall survival. Abstract: Acute lymphoblastic leukemia (ALL) patients who fail to acquire complete remission (CR) or who relapse after initial response have poor prognosis. At present there is no consensus as to the standard salvage therapy for these patients. In this study, we retrospectively evaluate safety and efficacy of a salvage regimen (CAGLP) consisting of G-CSF, low-dose cytarabine, aclarubicin, l -asparaginase and prednisone. Thirty-six patients were included with primary refractory (n = 13) or relapse (n = 23). The overall response rate (ORR) and CR rate were 86.1% and 63.9%, respectively. With a median follow-up of 34 months, the probability of overall survival (OS) at 2 years was 30% ± 10% and the disease-free survival (DFS) rate was 15% ± 8%. Treatment-related mortality was 5.6%. Our preliminary results indicated that CAGLP was feasible, safe and effective as a salvage reinduction chemotherapy for primary refractory and relapsed ALL patients.